Examining the role of the photopigment melanopsin in the striatal dopamine response to light - Gonzalez, L. Sofia; Fisher, Austen A.; Grover, Kassidy E.; Robinson, J. Elliott (Frontiers in Systems Neuroscience, 2025)
The mesolimbic dopamine system is a set of subcortical brain circuits that plays a key role in reward processing, reinforcement, associative learning, and behavioral responses to salient environmental events. In our previous studies of the dopaminergic response to salient visual stimuli, we observed that dopamine release in the lateral nucleus accumbens (LNAc) of mice encoded information about the rate and magnitude of rapid environmental luminance changes from darkness. Light-evoked dopamine responses were rate-dependent, robust to the time of testing or stimulus novelty, and required phototransduction by rod and cone opsins. However, it is unknown if these dopaminergic responses also involve non-visual opsins, such as melanopsin, the primary photopigment expressed by intrinsically photosensitive retinal ganglion cells (ipRGCs). In the current study, we evaluated the role of melanopsin in the dopaminergic response to light in the LNAc using the genetically encoded dopamine sensor dLight1 and fiber photometry. By measuring light-evoked dopamine responses across a broad irradiance and wavelength range in constitutive melanopsin (Opn4) knockout mice, we were able to provide new insights into the ability of non-visual opsins to regulate the mesolimbic dopamine response to visual stimuli.